The 3rd Symposium & Workshop on Molecular Pathology : book of abstracts and programme ; May 4-5, 2007, Olomouc, Czech Republic - Kolář, Zdeněk (Univerzita Palackého v Olomouci, 2007)
Abstrakta a program konference \\\"The 3rd Symposium and Workshop on Molecular Pathology\\\", konané 4.-5. 5. 2007 v Olomouci.
Keywords: Molecular Medicine; diagnostické techniky molekulární; molekulární medicína; molekulární biologie, molekulární medicína; Pathology, Clinical; Molecular Diagnostic Techniques; laboratorní medicína